Tourists Interest in Camping as an Alternative Tourism Activity During COVID-19 Pandemic: The AIDA Model Application - Ananda, Ayu; Novianti, Syifaa (Journal of Tourism Sustainability, 2021)
Since the coronavirus pandemic hit Indonesia, tourists have become more careful when doing tourist activities. Natural or outdoor tourist destinations are assumed as safe and preferable destinations because they have the lowest risk of coronavirus transmission. One of the activities that can be done in natural or outdoor tourist destinations is camping. Using the AIDA (Attention, Interest, Desire, and Action) Model, this research was conducted to determine how much tourists are interested in camping, especially in South Bandung, West Java, Indonesia, as it has many natural tourist destinations with camping areas. This study uses a quantitative descriptive method, frequency analysis techniques, and scoring analysis. Samples were taken using a stratified random sampling technique to 111 respondents. Respondents are tourists who know or have visited one of the three natural tourist destinations in South Bandung, used as samples, namely Mount Puntang, Ranca Upas, and Rancabali. The results show that tourists are quite interested in camping as an alternative tourism activity during the coronavirus pandemic. However, they have some limitations or prerequisites in visiting the camping area during these uncertain times.